Static Output Feedback Control Design for Descriptor Systems - Mohamed Yagoubi (Journal of Control Science and Engineering)
The static output feedback (SOF) synthesis problem for descriptor systems is considered in this paper. LMI-based algorithms are proposed to find potentially structured SOF gains ensuring admissibility and even H∞ performance of the closed-loop system. These algorithms are then used to propose a (descriptor) observer-based H∞ controller design method. An alternative technique for determining such separated estimation/control structure, after the design step, is also proposed. Several numerical examples, throughout the paper, demonstrate the effectiveness of the proposed algorithms.